Advancements in Inorganic Hole-Transport Materials for Perovskite Solar Cells: A Comparative Review - Johannes Zanoxolo Mbese (Energies)
Single-junction perovskite solar cells (PSCs) have been one of the most promising photovoltaic technologies owing to their high-power conversion efficiencies (PCEs) of ~27% and the low-cost fabrication processes involved, which pay off significantly given their distinct structural characteristics. Recently, inorganic hole-transport materials (HTMs) such as nickel oxide (NiOx) have been developed and received considerable attention for use in OPVs due to their excellent thermal stability, low-cost materials, and compatibility with scalable deposition methods. Here, we summarize the recent progress on inorganic HTMs for PSCs, which can be divided into three categories: NiOx, copper-based compounds, and emerging new alternatives. The deposition method (sputtering, atomic layer deposition, or a solution-based technique) is one of the most important factors affecting the performance and stability of PSCs. Finally, we review interfacial engineering strategies, such as surface modifications and doping, which can enhance charge transport and extend a device’s lifetime. We also balance the benefits of inorganic HTMs against the key challenges in advancing to commercialization, namely interior defects and environmental degradation. In this review, we summarize the recent progress and challenges toward developing cost-efficient and stable PSCs with inorganic HTMs and provide insights into the future development of these materials.